Nitrate variation in sudan hay bales from the same field - Carl H. Garten (Kansas Agricultural Experiment Station Research Reports, 1990)
Individual large round bales of sudan hay from the same cutting and field ranged from 1,525 to 6,250 ppm nitrate (NO3 ), with an average of 2,764 ppm. These results illustrate the substantial variability that can occur in the nitrate content of forage packages because of location in the field and serves to caution producers when feeding such forages.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Nitrate; Sudan; Forage Testing